Implications of Russia’s invasion of Ukraine for the governance of biodiversity conservation - Gallo-Cajiao, Eduardo; Dolšak, Nives; Prakash, Aseem; Mundkur, Taej; Harris, Paul G.; Mitchell, Ronald B.; Davidson, Nick; Hansen, Birgita; Woodworth, Bradley K.; Fuller, Richard A.; Price, Melissa; Petkov, Nicky; et al. (Frontiers in Conservation Science, 2023)
Maintaining peace and conserving biodiversity hinge on an international system of cooperation codified in institutions, but Russia’s invasion of Ukraine brings recent progress to a crossroads. Against this backdrop, we address some implications of Russia’s invasion of Ukraine for the governance of biodiversity conservation both within and beyond Russia. The Russian invasion of Ukraine threatens the governance system for biodiversity conservation, as it pertains to Russia and beyond, due to three interacting factors: (i) isolation of Russia from the international system, (ii) halt and delay of international cooperation, and (iii) changes in international and domestic policy priorities. We recommend making the existing international system of governance for conserving biodiversity more resilient and adaptable, while aligning security agendas with biodiversity conservation goals.